MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI RUPA MELALUI MEDIA RANCANGAN DI KELAS XI IPA 3 SMA ADABIAH PADANG - Yori Rayfandra, Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this study was to 1) increase student creativity and by using design media in class XI IPA 3 of Adabiah Padang High School. 2) Improve student learning outcomes by using design media in class XI IPA 3 of Adabiah Padang High School. The research method used is classroom action research. The research instrument were tests of student learning outcomes, students creativity questionnaires, observation sheets of student activities,observation sheets for teacher teaching activities, and data analysis. the results of this study state that. 1) the use of design media can increase the creativity of students in learning art in class XI IPA 3 Adabiah High School Padang. 2) the use of design media can improve student learning outcomes in learning art in class XI IPA 3 Adabiah High School Padang.Keywords: media design and learning outcomes are significant